Planning of a Hybrid Propulsion System for Purse Seine Fishing Vessels in Mayangan, Probolinggo, East Java - Hadi Prasutiyon; Arif Winarno; Semin Semin; Toto Soeharmono; Erik Sugianto (International Journal of Marine Engineering Innovation and Research, 2023)
The Mayangan Beach Fisheries Port (BFP) in Probolinggo City is a fishing port that was established using a combination of funds from the APBN, APBD of East Java province and APBD of Probolinggo city. Equipped with basic and functional facilities to support various fishing activities, fishing vessels generally use a mechanical propulsion system driven by a diesel engine. The results of the government's decision to increase fuel prices by 8,000 rupiah per liter, were then supported by a survey which showed that fishermen needed as much as 110 liters of fuel for a journey of approximately one hour for one trip, with these conditions making fishermen, especially in the Mayangan district, Probolinggo very objection by increasing the price of fuel that will be used to go to sea, so that with the problems complained of by fishermen on the Mayangan coast, Probolinggo about rising fuel prices, this refers to researchers planning a hybrid propulsion system to reduce consumption of the use of fuel that will be used for purse seine fishing boats. The results showed that the main engine specifications for the Mitsubishi ship were 6D24-Mpt (A) with 228 Kw power, then the Yanmar Ytg 15 Tlv generator, while the electric motor specifications that would be used were Weg Tru Metric 132 Kw / 175 HP, as well as batteries for storing battery energy which had specifications J185-Agm Vrla Agm / Non-Spillable. The difference in fuel consumption in the conventional system and the hybrid system looks quite significant. Using a hybrid propulsion system can produce fuel savings of up to 30% when compared to using a conventional engine.